Servicing `the other Hollywood - Ward, Susan; O' Regan, Tom (International journal of cultural studies, 2007)
Television programming has become such a significant part of Hollywood operations that Allen J. Scott has dubbed television production and distribution the 'other Hollywood'. However, it is also a sector that, over the 1900s, became subject to forces of decentralization as producers looked to alternative, more cost-efficient locations. Scott asks whether Hollywood is likely to face intensifying competition within global markets from regional production centres specializing in servicing international television production. This study charts the changing push and pull factors that directed 'runaway' television production to, and then away from, one such regional production centre - the Gold Coast, Australia. This regional centre's mixed history with international production suggests the need to attend to both processes of decentralization and recentralization of production. The article concludes that concerns over potential competition to Hollywood emerging from production locations like the Gold Coast may be overstated. [Reprinted by permission of Sage Publications Ltd., copyright 2007.]